O uso da internet como instrumento na prestação de serviços públicos na Prefeitura Municipal de Belo Horizonte através do Sistema de Atendimento ao Cidadão - Eliana Castro Coelho (2007)
This study had the objective of analyzing the reasons for the low use of the Internet as a channel of access to a group of public services from the city of Belo Horizonte - Brazil, as opposed to other traditional channels such as the telephone or presencial access. Using case study methodology, 163 users of telephone access and 37 presencial userswere interviewed. The results show that the average age is higher for presencial users. The majority of telephone and presencial users has a high school or university degree but presencial users have a lower educational level. 57% of the telephone users and 34% of presencial users have Internet access and use it for several tasks. As for the useof the Internet, 64% of both telephone and presencial users, utilize it or have utilized it. The research concludes that the majority of the users have the capability of utilizing the Internet but, in fact, asked for the services by telephone or presencially. It is important to note that 80% of users did not know about the availability of the services in the Internet and more than 90% have never accessed the site of the City of Belo Horizonte.Considering these results, it is recommended that decision makers in the area of egovernment take a proactive attitude concerning the offer of electronic services and pay attention to their role and social responsibility as change agents.